IZALPININ FROM FRUITS OF ALPINIA OXYPHYLLA WITH ANTAGONISTIC ACTIVITY AGAINST THE RAT BLADDER CONTRACTILITY - Yuan, Yuan; Tan, Yinfeng; Xu, Peng; Li, Hailong; Li, Yong-Hui; Zhang, Junqing; Zhang, Jun-Qing; Chen, Feng; Huang, Guo-Jun (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Alpinia oxyphylla (Zingiberaceae), an herbaceous perennial plant, its capsular fruit is commonly used in traditional Chinese medicine for the treatment of different urinary incontinence symptoms including frequency, urgency and nocturia. These symptoms are similar to the overactive bladder syndrome. In our lab, we found that the 95% ethanol extract of the capsular fruits exhibited significant anti-muscarinic activity. Some constituents in capsular fruits including flavonoids (e.g., izalpinin and tectochrysin), diarylheptanoids (e.g., yakuchinone A and yakuchinone B) and sesquiterpenes (e.g., nootkatone), are regarded as representative chemicals with putative pharmacological activities. Objective: This study aimed to evaluate the in vitro antagonistic actions of izalpinin on carbachol-induced contraction of the rat detrusor muscle. Materials and Methods: In vitro inhibition of rat detrusor contractile response to carbachol was used to study the functional activity of izalpinin. The isolated detrusor strips of rats were mounted in organ baths containing oxygenated Krebs’ solution. The cumulative consecutive concentration-response curves to carbachol-evoked contractions in strips of rat bladder were obtained. Results: Carbachol induced concentration-dependent contractions of isolated rat bladder detrusor strips. The vehicle DMSO had no impact on the contraction response. The contraction effects were concentration-dependently antagonized by izalpinin, with a mean EC50 value of 0.35 µM. The corresponding cumulative agonist concentration-response curves shifted right-ward. Conclusions: Izalpinin exhibits inhibitory role of muscarinic receptor-related detrusor contractile activity, and it may be a promising lead compound to treat overactive bladder.